PEMERIKSAAN CD4 HUBUNGANNYA DENGAN STADIUM PENYAKIT HIV PENDERITA - Adi K. Aman; Tonny .; Rachmad . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
The accurate measuring CD4 are important for knowing immune system from HIV infected person. Because there are increasing clinical complication with decreasing of CD4. Measuring of CD4 also useful for the decisions when therapy of ART started and monitoringefficacy of the medication. Also it is necessary to know CD4 and its relations to HIV stadium in HIV positive patients at Adam MalikGeneral Hospital Medan. The CD4 examination used in EDTA blood. Immunophenotyping examination carried out by Flow CytometryBD FACS CaliburTM used TritestTM BD reagent CD3/CD4/CD45 without true count tube. From 515 HIV patients, 80.5% are men, 86%from all patients between 20-40 years old with biggest risk factor are heterosexual. From 250 patients that examination of CD4, 81%patients are stadium I had amount CD4 > 350/mm. Examination of CD4 arethe important parameter to follow up condition of HIV patient for prevented not become worse, also knowing diseases progressivismand therapy progress.3 and patients stadium III had amount CD4 < 200/mm3